Inspire Certification Among Pediatric Hematology Oncology Nurses. (September 2019) - Altounji, Diane; Williams, Sonya; Secola, Rita
Professional certification validates nurses' knowledge and expertise in their specialty. In support of professional development, nursing excellence as a Magnet® designated hospital, and commitment to improve patient outcomes, increasing the number of certified pediatric hematology oncology nurses at Children's Hospital Los Angeles is a priority. Expert certified nurses and educators assessed current staff nurse perceptions of and motivations for becoming certified. A nurse survey was completed, and the results identified barriers to certification and the need for an onsite review course to encourage more nurses to take the Certified Pediatric Hematology Oncology Nurse (CPHON®) exam. The Oncology Nursing Certification Corporation (ONCC) CPHON® test blueprint guided the development of the Children's Hospital Los Angeles review course curriculum. Certified nurse experts volunteered as course instructors to present an overview of pediatric cancer, pediatric hematology, psychosocial review, chemotherapy and related medications, and long-term effects. In addition to course didactics, interactive learning sessions were included to allow participants to question, discuss, and apply new knowledge. Sample test questions were provided to each participant for independent study post–course attendance. Each participant completed course evaluations to measure the usefulness of the content, environment, and teaching methods. Since the implementation of this course, the overall number of certified hematology oncology nurses has increased by 15.3%.